The COVID-19 pandemic and changes in eating habits of Brazilian adolescents - Crizian Saar Gomes; Nathália Mota Mattos Santi; Danilo Rodrigues Pereira da Silva; André Oliveira Werneck; Célia Landmann Szwarcwald; Marilisa Berti de Azevedo Barros; Deborah Carvalho Malta (Elsevier, 2022)
Introduction: The social distancing imposed by the COVID-19 pandemic influenced lifestyle and modified dietary patterns. Our objective was to evaluate the consumption of fruits and vegetables (FV), and ultra-processed foods (UPF), before and after the COVID-19 pandemic, as well as to identify the sociodemographic factors associated. Methods: This study used data from the "Convid Adolescents", a survey on health behaviors that were collected through an online questionnaire self-completed by 9.470 adolescents between 12 and 17 years of age during the pandemic in Brazil in 2020. Individuals were invited to participate through a chain-sampling procedure called "virtual snowballing". Information about FV, and UPF consumption before and during the pandemic period were reported. The independent variables used were sex, age group, race/color of skin, kind of school, education level of the mother, region of Brazil, financial difficulties during the pandemic, food insecurity, and social restrictions. Logistic regression models were used. Results: There was a reduction in the low consumption of FV (83.5% to 80.3%) and there was no significant difference in the high consumption of UPF (38.9% to 38.1%) before and during the pandemic. The incidence of low consumption of FV and high consumption of UPF during the pandemic was 20% and 13.8%, respectively. Girls, private school adolescents, who reported having food insecurity and financial difficulties during the pandemic were the most affected subgroups. Conclusions: Despite little change in the prevalence of FV and UPF consumption before and during the pandemic, the incidence of high consumption of UPF and low FV consumption was high, and it identified in specific population subgroups.